Assessment of serum galectin-3 levels in acute rheumatic fever - Epçaçan, Serdar; Ramoğlu, Mehmet Gökhan; Epçaçan, Zerrin Karakuş; Baskın, Avniye Kübra (The Turkish Journal of Pediatrics, 2022)
Background. Galectin-3 is a biomarker which takes a role in both acute and chronic inflammation as well as fibrosis and oxidative stress. Increased levels of it are associated with cardiovascular diseases. This study was performed to investigate the levels of galectin-3 in acute rheumatic fever (ARF). Methods. 30 patients with ARF and 26 healthy children were included. Galectin-3 levels of the patients were compared with the controls, as well as within the patients before and after the treatment. Results. The patients had significantly lower galectin-3 levels on admission than the control (p=0.02), but its levels were not significantly different between these groups at the end of treatment (p=0.714). The mean galectin-3 levels of the patients were increased after the treatment (p < 0.001). Severity of carditis and galectin-3 levels were negatively correlated (r=-539, p=0.02). Conclusions. Children with ARF have significantly reduced levels of galectin-3 and there is a negative correlation between the severity of the carditis and galectin-3 levels. Studies with larger sample sizes may give more accurate data about the role of galectin-3 in ARF.